2004
DOI: 10.1002/ejic.200300648
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of Octahedral Metal Compounds − Equilibrium, Crystal and Molecular Structure of Nickel(II) Complexes of Linear N2O4, N4S2 or N6 Donors Set Atoms Ligands

Abstract: 2+ complex, however, the size of the thioether sulfur atoms imposes a C 2v symmetry; the pyridyl groups and the sulfur atoms are in trans positions and all

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Ni–O2, −O4, −N1, −N2, −N3, and −N4 distances in the [Ni( l -Tyr) 2 (bpy)] unit ( 1 ; Table ) are all different; thus, the symmetry around the six-coordinated Ni 2+ center is only C 1 . The noticeable asymmetry of the d–d bands indicates that those bands are probably split under crystal-field symmetry lower than O h . This spectrum was thus filtered for the purpose of obtaining the refined band splitting and energies of its components. The filtering process revealed that the first d–d band is composed of three maxima at 9460, 10650, and 11210 cm –1 (Figure and Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ni–O2, −O4, −N1, −N2, −N3, and −N4 distances in the [Ni( l -Tyr) 2 (bpy)] unit ( 1 ; Table ) are all different; thus, the symmetry around the six-coordinated Ni 2+ center is only C 1 . The noticeable asymmetry of the d–d bands indicates that those bands are probably split under crystal-field symmetry lower than O h . This spectrum was thus filtered for the purpose of obtaining the refined band splitting and energies of its components. The filtering process revealed that the first d–d band is composed of three maxima at 9460, 10650, and 11210 cm –1 (Figure and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In D 2 h ( C 2 ″) symmetry, the 3 B 1g term is the ground state and nine spin-allowed transitions, 3 B 1g → 3 A g , 3 B 1g → 3 B 2g , and 3 B 1g → 3 B 3g (I st d–d), 3 B 1g → 3 B 1g , 3 B 1g → 3 B 2g , and 3 B 1g → 3 B 3g (II d–d), 3 B 1g → 3 B 1g , 3 B 1g → 3 B 2g , and 3 B 1g → 3 B 3g (III d–d), are possible as a result of splitting of 3 T 2g ( 3 F, O h ), 3 T 1g ( 3 F, O h ), and 3 T 1g ( 3 P, O h ) states in a rhombic crystal field (Table ). The three components of the I d–d band are centered at 9460, 10650, and 11210 cm –1 , respectively. The II d–d band includes three separate components obtained at 16060, 17100, and 18600 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the coordination of Ni- [4], and Cu-and Zn-atoms [5] with linear hexadendate ligands involving two pyridinylmethyl groups and containing donor N-and O-atoms or N-and S-atoms. These studies show that the thermodynamic stability, the structural configuration, and the redox properties of these mononuclear complexes depend on the nature of the two central donor heteroatoms.…”
mentioning
confidence: 99%